Self-cross-linked melamine-formaldehyde-pectin aerogel with excellent water resistance and flame retardancy. (15th February 2019) - Chen, Hong-Bing; Li, Xin-Lei; Chen, Ming-Jun; He, Yan-Rong; Zhao, Hai-Bo
Highlights: Self-cross-linked aerogel based on pectin and melamine-formaldehyde resin was fabricated. MF-pectin aerogels have significantly increased compressive moduli. MF-pectin aerogels possess excellent water resistance and low flammability. Abstract: Self-cross-linked aerogel based on pectin and melamine-formaldehyde resin (MF) was fabricated via freeze-drying method using water as solvent, where pectin is structural material meanwhile acting as acid to catalyse the cross-linking of MF. The cross-linking reaction easily occurs without additional additives, which can be significantly accelerated at elevated temperatures, with a critical value of about 55 °C. The obtained aerogel shows network microstructures as observed with SEM. With increasing pectin content, the aerogel shows significantly increased compressive modulus. The compressive modulus of M10Pe5 arrives 23.2 MPa, the specific modulus of which arrives 188 MPa cm 3 /g, while pure MF aerogel are too fragile to keep intact after freeze-dried. The resulting aerogel has good thermal stability, excellent water resistance (can be second dried with limited strength loss) and low flammability. This partially bio-based novel aerogel with impressive properties is promising in many applications.